Peningkatan Produktivitas Pemasaran Produk UMKM Pempek Acen dengan Pendekatan Analisis SWOT dan DMAIC - Liyanto, Fandy; Pratama, Yohanes Dicka (Jurnal PASTI (Penelitian dan Aplikasi Sistem dan Teknik Industri), 2020)
After conducting interviews it is known that the marketing activities implemented by Pempek Acen SME’s have not been running optimally so that it causes the low profits obtained by Pempek Acen SME’s. To formulate an appropriate marketing strategy, a SWOT analysis is carried out to determine the strengths, weaknesses, opportunities and threats of Pempek Acen SME’s. Then an improvement is made using the DMAIC structure. First the identification of current conditions at SMEs is carried out, then measurements are made to select the issues to be overcome, then analyze the main causes of problems using a fishbone chart, then improvements are made. Implementation of improvements carried out include conducting promotional activities using social media, making coupons for customers who buy back Pempek SME’s Pempek Acen products and adding pempek variants to Pempek Acen SME’s products. After the implementation of the improvement, there was a decrease in the gap between the number of products produced and sold, an increase in the level of customer loyalty and an increase in productivity of 1,10235 to 1,13714 after implementation of the improvements. From these data, it can be seen an increase in productivity by 0.03479 or equivalent to 3.479%.